Idealisme Sosial Kemasyarakatan dalam Kitab Hidayatus Shalikin karangan Syaikh Abdus Shamad Al-Palimbani - Pramasto, Arafah (Analisis: Jurnal Studi Keislaman, 2020)
Sufism is a kind of appreciation of the esoteric dimension of Islam which is often considered a destructive and distorted teaching. A sharp criticism was raised by Hasan Hanafi, a modern Muslim intellectual from Egypt, according to Sufism arising from the despair of the opponents of the absolutism of the Umayyads, and this Sufism had no social contribution. However, in Indonesia there is a cleric from Palembang named Shaykh Abdus Shamad Al-Palimbani who adheres to the Neo-Sufism style with its characteristic namely activism in collective life. This article seeks how to uncover the form of social idealism in the book Hidayatus Shalikin by Shaykh Abdus Shamad Al-Palimbani in the 18th century. The research methodology used is the historical method, heuristic, critical interpretation, and Historiography.The results of this study prove that Shaykh Abdus Shamad's social idealism includes several aspects, namely universal compassion in the morality of the people, rejecting violence and oppression, clean assets from acts of wrongdoing, and forbidding lies and expressions of hatred in the community.